Medical Liability in Sinus Surgery: A Westlaw Database Analysis From 2000 to 2017. Issue 5 (September 2020) - Shah, Suparna N.; Ramirez, Arianna V.; Haroun, Kareem B.; Chaaban, Mohamad R.
Background: Medical malpractice occurs when a hospital or health-care provider through negligent act or omission results in an injury to a patient. More than 50% of otolaryngologists have faced at least 1 claim, with rhinology being the most litigated subspecialty. This study aims to analyze medical litigation trends in Rhinology from 2000 to 2017 in the United States. Methods: The Westlaw database was reviewed from 2000 to 2017. Data were compiled on the demographics of the plaintiffs, procedures, nature of damages, legal allegations, and the use of expert witnesses, physician demographics/practice characteristics, verdicts, indemnities, and county/state of case. Results: There were 75 cases that met inclusion criteria after review of 125 cases. Majority of cases went to trial over settlement (80%) and were found in the Northeast region of the United States (36%). Most common cited legal allegations were improper performance and failure to follow standard of care. The most common nature of injuries were eye injury (29%) and intracranial complications (27%). The highest payouts were for progression of disease followed by intracranial injury. Of the 75 total cases analyzed, 37 (49.3%) used expert witnesses. When an expert witness was used at trial, the verdict statistically favored the defendant (62.5%). Conclusions: Our analysis reveals the importance of meticulous surgical techniques and thorough preoperative evaluations.